Implementasi Jaringan Point to Multipoint Menggunakan Metode NDLC - Anto, Mardianto (MULTINETICS, 2022)
A point-to-multipoint network is a wireless internet network from one radio access point that is connected to several radio access points located in several locations that are quite far away, and not possible via network cables. To build an internet network within the USN Kolaka campus using cables, it is necessary to provide a lot of cables as well as complex configurations and installations. Based on the problem of connecting a centralized internet network from the UPT-TIK building to the Faculty of Information Technology and Faculty of Social and Political Sciences buildings with easier configuration and installation, it is necessary to implement a point-to-multi point network using the method Network Development Life Cycle (NDLC). From the results of the study it was concluded that the connectionpoint-to-multipointis the right solution to connect areas that are far apart between the UPT-TIK building and the receiving building of the Faculty of Information Technology and the Faculty of Social and Political Sciences so that it is more efficient to use cables and can facilitate configuration and installation.